OLAH VISUAL EFEK LIMBAH KARAT MENGGUNAKAN TEKNIK RUST DYEING UNTUK PRODUK PUFFER JACKET - Orizza Anggun Ferayanti (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
Rust dyeing is a fabric coloring technique using rust which is a potential alternative dye, has high aesthetic value, and can create unique and interesting visualizations because the resulting color effects are different.The aim of this design is to use rust for rust dyeing motifs so that they have higher use value. The visual motifs displayed were obtained from exploration results using various binding techniques. The rust dyeing motif was implemented on the puffer jacket to add to its aesthetic value. The design method used is the creation approach method according to Gustami which consists of three stages, namely exploration, design stage (putting found ideas into visual form), embodiment stage (making selected plans and designs into realwork). The result of this design is a rust dyeing motif fabric which is used as an aesthetic complement to puffer jacket products using rust dyeing and quilting techniques.